Thesaurus on Philippine tobacco - Tacderan, Evelyn E. (Institute of Library Science, University of the Philippines Diliman, 1988)
The Thesaurus on Philippine Tobacco, which consists of 1,630 scientific and technical terms on tobacco, was compiled to develop a controlled vocabulary on Philippine tobacco based on the available scientific literature in the different disciplines; to facilitate documentation and retrieval of tobacco information; and to promote standardization of terms in the literature.